La prévalence de l’artériopathie oblitérante des membres inférieurs au cours de l’accident vasculaire cérébral ischémique. - BENNACEUR Afaf Yassmine; DEBBA Imane Sassia; RIGHI Ahmed Yassine (Université Amar Télidji Laghouat, 2023)
Introduction: Lower extremity artery disease is a marker of systemic atherosclerosis. It is a common and serious disease that shares with cerebrovascular and coronary disease a high risk of mortality. Material and Method: This is a prospective observational study on 30 patients for AVCI, carried out over a period of 09 months from 10/07/2022 to 30/04/2023 in the unit of Internal Medicine at the level of the Mixed Hospital 240 bed “Colonel Lotfi” – Laghouat. Results: The prevalence of LEAD was 16.7% n=5, among them 03 women and 02 men. The age group most affected was “over 60 years” with a median age of 70. 60% of patients were hypertensive, 36.7% of patients were diabetic, 40% were obese. The median Hba1c was 6.1%, the median cholesterol 1.55 g/l and the median PT 90%, the CRP was positive in 48.3%. The artery most affected was the MCA with a percentage of 70.4%. There was a significant correlation with the development of LEAD for Covid- 19 p=0.047 and Hba1c p=0.021.
30cm CD-ROM